Microbial infections in eight genomic subtypes of chronic fatigue syndrome/myalgic encephalomyelitis. Issue 2 (2nd December 2009) - Zhang, Lihan; Gough, John; Christmas, David; Mattey, Derek L; Richards, Selwyn C M; Main, Janice; Enlander, Derek; Honeybourne, David; Ayres, Jon G; Nutt, David J; Kerr, Jonathan R
Abstract : Background: The authors have previously reported genomic subtypes of chronic fatigue syndrome/myalgic encephalomyelitis (CFS/ME) based on expression of 88 human genes. Aim: To attempt to reproduce these findings, determine the specificity of this signature to CFS/ME, and test for associations between CFS/ME subtype and infection. Methods: Expression levels of 88 human genes were determined in blood of 62 new patients with idiopathic CFS/ME (according to Fukuda criteria), six patients with Q-fever-associated CFS/ME from the Birmingham Q-fever outbreak (according to Fukuda criteria), 14 patients with endogenous depression (according to DSM-IV criteria) and 29 normal blood donors. Results: In patients with CFS/ME, differential expression was confirmed for all 88 genes. Q-CFS/ME had similar patterns of gene expression to idiopathic CFS/ME. Gene expression in patients with endogenous depression was similar to that in the normal controls, except for upregulation of five genes ( APP, CREBBP, GNAS, PDCD2 and PDCD6 ). Clustering of combined gene data in CFS/ME patients for this and the authors' previous study (117 CFS/ME patients) revealed genomic subtypes with distinct differences in SF36 scores, clinical phenotypes, severity and geographical distribution. Antibody testing for Epstein–Barr virus, enterovirus, Coxiella burnetii and parvovirus B19 revealed evidence of subtype-specific relationships for Epstein–Barr virus and enterovirus, the two most common infectious triggers of CFS/ME. Conclusions: This study confirms the involvement of these genes in CFS/ME.